Dermatosparaxis (Ehlers–Danlos Type VIIC): Prenatal Diagnosis Following a Previous Pregnancy With Unexpected Skull Fractures at Delivery. Issue 5 (13th March 2013) - Solomons, Joyce; Coucke, Paul; Symoens, Sofie; Cohen, Marta C.; Pope, F. Michael; Wagner, Bart E.; Sobey, Glenda; Black, Rebecca; Cilliers, Deirdre
Abstract Dermatosparaxis Ehlers–Danlos syndrome (or EDS VIIC), a rare autosomal recessive connective tissue disorder, is characterized by extreme skin fragility, premature rupture of membranes in pregnancy, and spontaneous rupture of internal organs. Here we report a second patient with EDS VIIC presenting with congenital skull fractures and skin lacerations at birth, complications which may occur more frequently than previously thought in this condition. We also discuss the role of prenatal diagnosis in the management of a subsequent normal pregnancy. © 2013 Wiley Periodicals, Inc.